Functional gold nanoclusters as antimicrobial agents for antibiotic-resistant bacteria. (July 2010) - Chen, Wei-Yu; Lin, Ju-Yu; Chen, Wei-Jen; Luo, Liyang; Wei-Guang Diau, Eric; Chen, Yu-Chie
Aims: Our aim was to demonstrate that lysozyme-directed generation of gold nanoclusters (Au NCs) are potential antimicrobial agents for antibiotic-resistant bacteria and broad labeling agents for pathogenic bacteria.Materials & methods: Lysozyme is an enzyme that is capable of hydrolyzing the cell walls of bacteria. In this study, we demonstrated the generation of functional Au NCs by using lysozyme as the sequester and the reducing agent for Au precursors at 40°C. In addition, to shorten the reaction time, the reaction was conducted under microwave irradiation within a short period of time for the first time.Results: The bioactivity of the lysozyme on the Au NCs was retained. Therefore, the as-prepared lysozyme–Au NCs with desirable fluorescence feature were successfully employed to be broad-band labeling agents for pathogenic bacteria. Furthermore, we also demonstrated that the lysozyme–Au NCs can be used to effectively inhibit the cell growth of notorious antibiotic-resistant bacteria, including pan-drug-resistant Acinetobacter baumannii and vancomycin-resistant Enterococcus faecalis .Conclusion: The potential of employing the lysozyme–Au NCs for bacterial labeling and as antimicrobial agents is expected.